Kemampuan Profitabilitas sebagai Variabel Moderasi antara Corporate Philanthrophy dan Kepemilikan Institusional dengan Nilai Perusahaan - Masruroh (IAIN Madura, 2022)
This study aimed to analyze the effect of Corporate Philanthropy and Institutional Owners on the firm value to Profitability as a moderating variable. This study using a secondary data. The population of this research are the manufactured companies listed on Indonesia Stock Exchange during the years 2014-2018. The sampling method using is purposive sampling method. Based on the criteria using, the company qualified research sample is 22 companies. The analysis method using in this study is Moderating Regression Analysis, model feasibility test and t-test. Based on f-test, Corporate Philanthropy, Institutional Owners, and Corporate Philanthropy and Institutional Owners that is moderated Profitability significant effect to firm value. Based on t-test, Corporate Philanthropy doesn’t significant effect to firm value, Institutional Owners doesn’t significant effect to firm value, Corporate Philanthropy that is moderated Profitability doesn’t significant effect to firm value, while Institutional Owners has a negative and significant effect to firm value